Comparative Assessment of Soil Organic Carbon Stock Potential under Agroforestry Practices and Other Land Uses in Lowlands of Bale - Mengistu, Bikila; Asfaw, Zebene (International Journal of Environment, 2017)
Soil organic carbon is the carbon associated with soil organic matter that is made up of decomposed plant and animal materials. This study was conducted in Dallo Mena district to estimate the amount of soil carbon stock stored in shade grown coffee (SC) and homegarden agroforestry practices (HG), and adjacent natural forest (NF) and annual crop field (CF) and to show the potential of agroforestry practices in soil organic carbon storage capacity. The study site was selected based on spatial analogue approach. From each land uses nine plots were selected by using systematic sampling method following the transect line. Soil organic carbon stock (100cm depth) were the highest for the NF(170.11 ± 14.59 Mg ha-1), followed by SC(127.96 ± 9.43 Mg ha-1), HG(107.62 ± 12.55 Mg ha-1) and CF(97.56 ± 6.85 Mg ha-1). Agroforestry and other land uses of Dallo Mena districts are providing various ecological as well as economical benefits for the community. It is used as income source, conserving different plant species diversity and at the same time storing large amounts of soil organic carbon. Therefore, there is significant difference among natural forest, shade grown coffee agroforestry practice, homegarden agroforestry practice and annual crop field in soil organic carbon storage capacity.International Journal of EnvironmentVolume-6, Issue-3, Jun-Aug 2017, page: 1-14